2023
DOI: 10.1371/journal.pone.0285037
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of healthy volunteer experience receiving subcutaneous infusions of high-dose benzathine penicillin G (SCIP) provides insights into design of late phase clinical studies

Abstract: Introduction Secondary prophylaxis to prevent rheumatic heart disease (RHD) progression, in the form of four-weekly intramuscular benzathine benzylpenicillin G (BPG) injections, has remained unchanged since 1955. Qualitative investigations into patient preference have highlighted the need for long-acting penicillins to be delivered less frequently, ideally with reduced pain. We describe the experience of healthy volunteers participating in a phase-I safety, tolerability and pharmacokinetic trial of subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Administering BPG through a series of slow pushes enabled greater control in the rate of delivery in comparison to the spring infuser used in the Phase-I trial. This potentially led to slightly shorter injection times; Phase-I mean time of 22 minutes, range 16–29 minutes [ 21 ], compared to a mean of 15 minutes, range of 9–25 minutes, in Phase-II. In addition, participants in the Phase-II trial reported slightly lower pain scores during the injection in comparison to the Phase-I trial (median NRS 1.0, range 0–7 median compared to median NRS 2.5, range 0–8) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administering BPG through a series of slow pushes enabled greater control in the rate of delivery in comparison to the spring infuser used in the Phase-I trial. This potentially led to slightly shorter injection times; Phase-I mean time of 22 minutes, range 16–29 minutes [ 21 ], compared to a mean of 15 minutes, range of 9–25 minutes, in Phase-II. In addition, participants in the Phase-II trial reported slightly lower pain scores during the injection in comparison to the Phase-I trial (median NRS 1.0, range 0–7 median compared to median NRS 2.5, range 0–8) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that delivering high-dose BPG by SC infusion was safe, had acceptable tolerability and could be suitable for up to three-monthly dosing intervals for secondary prophylaxis of ARF/RHD [ 20 ]. In addition to the Phase-I trial, a qualitative sub-study was undertaken to provide in-depth information about the tolerability and acceptability of the delivery method [ 21 ]. The sub-study demonstrated that the procedure was acceptable to participants, and while some experienced high pain levels, most had tolerable mild discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…By delivering BPG through a series of slow pushes there was a greater control, in comparison to the spring infuser used in SCIP-I, over the rate the BPG was delivered. This potentially led to slightly shorter infusion times; SCIP-I - mean infusion time of 22 minutes, range 16-29 minutes [20], compared to a mean of 15 minutes, range of 9-25 minutes, in SCIP-II. In addition, participants in SCIP-II reported slightly lower pain scores during the infusion in comparison to SCIP-I (median NRS 1.0, range 0-7 median compared to median NRS 2.5, range 0-8) [19].…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that delivering high-dose SCIP was safe, had acceptable tolerability and could be suitable for up to three-monthly dosing intervals for secondary prophylaxis of ARF/RHD [19]. In addition to the Phase-I trial, a qualitative sub-study was undertaken to provide in-depth information about the tolerability and acceptability of SCIP [20]. The sub-study demonstrated that SCIP was acceptable to participants, and while some experienced higher pain levels, most had tolerable mild discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Interviews were recorded, transcribed verbatim, and analyzed using thematic analysis. The qualitative assessment of the volunteer experience of SCIP has been reported separately ( 32 ).…”
Section: Methodsmentioning
confidence: 99%